Internal Audit in ERP Systems Context - Roxana Dana IGNA; Bogdan Stefan IONESCU (Audit Financiar, 2021)
Through this paper, the authors wanted to highlight how important and useful are ERP systems for any company that requires internal auditing. ERP - Enterprise Resource Planning systems are intelligent software that can be adapted to the needs of each company allowing the combination of all business processes in a single database. They are also a way of internal control over the data entered and employees. From an internal audit perspective, these systems can be considered an appropriate solution because they provide an opportunity to more effectively manage internal and external audit risks. The main objective of this paper is to demonstrate the satisfaction of internal audit needs with the help of integrated systems. These systems facilitate the operation of data and their security. Another objective was to analyse how much these systems can reduce certain risks. The risks of significant misstatement may be mitigated by these systems, and any operation introduced may be analysed, verified and approved / disapproved. Therefore, a quantitative research was conducted, using the questionnaire as an analysis tool. Based on the answers received, the profile of the respondents was outlined and at the same time a statistical analysis was performed. The results obtained demonstrate that respondents appreciate ERP systems’ utility. They perceive a reduction in financial and operational risk but also an increase in technical risk. Of course, these technical risk issues can be mitigated by the internal audit department's ability to assess and manage any issues that may arise. However, respondents also emphasize the need of training employees in using the system and understanding the data generated by it. Without well-trained employees, performance at the company level, as well as at the internal audit level would not be achieved. It is essential to have training at employees’ level who manage data in an ERP system. This training is also valid for internal auditors who can recommend this system to reduce audit risks.